DETERMINAN KUALITAS HASIL PEMERIKSAAN PAJAK MELALUI PENERAPAN NILAI-NILAI ETIK KEMENTERIAN KEUANGAN - Ardi Susilo, Irawan; Parulian Ompusunggu, Arles; Djaddang, Syahril (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This research aims to examine and analyze the influence of tax auditor's competence and motivation toward tax audit quality, through the implementation of the "Ethical Values of Ministry of Finance" as mediation in The Regional Tax Office of Jakarta Selatan I. Data used in this research is primary data obtained through questionnaires from 143 tax auditors in eight tax offices located in The Regional Tax Office of Jakarta Selatan I as respondents. The data obtained were analyzed using Path Analysis using Linear Structural Relations (Lisrel) 8.80 software. The result of this research shows that tax auditor's competence have no significant influence on tax audit quality, while tax auditor's motivation have significant influence toward tax audit quality. In indirect relationship, both of tax auditor's competence and tax auditor's motivation have significant influence on tax audit quality, through the implementation of the "Ethical Values of Ministry of Finance". Implementation of the "Ethical Values of Ministry of Finance" directly also have significant influence on tax audit quality in The Regional Tax Office of Jakarta Selatan I.